New Venture Creation Determinant Factors of Social Muslimpreneurs - Seun, AO; Kalsom, AW (Univ Putra Malaysia Press, 2024)
This study aims to investigate new venture determinant factors of Muslimpreneurs. Muslimpreneurs is conceptualised as capabilities of driving innovative societal change on the principles of the al-Quran and al-Sunah not solely for profit, but above all to benefit all of mankind. The two main research questions are, "What factors determine new venture creation?" and "Does training moderate new venture creation?" The study employs the hypothetical deductive approach using the multivariate regressions analysis. Four constructs, namely, Islamic motivation, entrepreneurial capabilities, Muslimpreneur characteristics and social capital are regressed as determinants of new venture creation readiness. Data were gathered from Universiti Sains Islam Malaysia students across all faculties (N=439). The results reveal that all factors are significantly related to new venture creation except social capital and training does moderate the relationship. The findings might be helpful in developing Muslimpreneurs as the main players of Islamic entrepreneurialism that would be the thrust of social enterprises development.